New taxa of Afrotropical Toktokkies (Coleoptera: Tenebrionidae: Molurina) from the Natural History Museum of Basel - Kamiński, Marcin Jan (Zootaxa, 2024)
Investigation of the darkling beetle (Tenebrionidae) specimens from the Natural History Museum Basel (Switzerland) resulted in the discovery of two new species of Afrotropical toktokkies (tribe Sepidiini). Both taxa provided novel morphological data which, in the light of previously acquired molecular evidence, challenged the taxonomic coherence of the genus Dichtha. To accommodate this information a new genus Bouchardium gen. nov. is hereby proposed. The three following species were assigned to this new genus: Bouchardium chillygonzalesi sp. nov. (type species), B. cubicum (Guérin-Méneville, 1845) comb. nov. (transferred from Dichtha), B. mariae sp. nov. The placement of Bouchardium within the subtribe Molurina is briefly discussed. Additionally, a new species of the genus Toktokkus (T. zofiae sp. nov.) is described from South Africa.